Distance friction and the cost of hunting in tropical forests (2012)
Empirical studies of tropical forest hunting have shown the existence of marked spatial gradients of hunting effort, game harvest, and animal abundance, as hunters mostly hunt near villages, roads, and rivers. The mechanisms underlying these patterns have, however, hitherto been poorly known. This article presents a spatial bioeconomic model based on the concept of distance friction, i.e. an increasing marginal cost of distance. The model is validated by comparison with an economic field experiment with Amazonian hunters and with previous empirical data on hunting.